THE RATE OF ECONOMIC GROWTH, MSES AND HOUSEHOLD CONSUMPTION EXPENDITURE ON THE NUMBER OF POOR PEOPLE IN LAMPUNG PROVINCE - Oky Indrajaya; Neli Aida; Asih Murwiati (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the influence of Gross Regional Domestic Product (GDP) per capita, Regency/City Minimum Wage (MSE), and Household Consumption Expenditure (PKRT) on poverty levels in Lampung Province during the period 2010–2024. Using the panel data regression method and the Fixed Effect Model (FEM) approach, this study utilizes data from six districts/cities selected based on the socioeconomic diversity of the region. The results of the study show that GDP has a negative and significant effect on the poverty rate, indicating that economic growth plays an important role in reducing the number of poor people. On the contrary, MSEs have a positive and significant effect, which indicates that the increase in the minimum wage has not been able to reduce poverty, especially in areas with the dominance of the informal sector. Meanwhile, PKRT did not show a significant influence on poverty. These findings show that poverty alleviation efforts in the regions need to be directed towards inclusive economic growth, wage policies that are adaptive to local employment structures, and sustainable strengthening of household consumption capacity.